A comparison of the Effects of Lemon Peel -Silver Nanoparticles Versus Brand Toothpastes and Mouthwashes on Staphylococcus Spp. Isolated From Teeth Caries - Ahmed, Mais E.; Salama, Khadija (Iraqi Journal of Science, 2020)
Thirty one samples of gum swabs were collected from patients with tooth caries (5-30 years old) from the College of Science (Biology department )- University of Baghdad- Iraq for the period from October 2018 to December 2018. , The samples were transported, after inoculation in a transport media (nutrient broth), to the laboratory of the College of Science and then cultured on mannitol salt agar and blood agar). The isolates belonging to Staphylococcus spp. were identified by biochemical tests and Vitek 2 compact system, while the more antibiotic resistant isolates were identified by using Polymerase Chain Reaction(ï´¾PCR) and sequencing of 16SrRNA . The results showed sharp UV absorption peaks at 330 - 340nm and AFM at 56 nm. Transmission Electron Microscope (TEM) results showed that lemon silver nanoparticles (NPs) are spherical in shape. The results also demonstrated that the silver NPs have a higher antibacterial activity with a diameter of inhibition zone that reached 16mm as compared with the common three mouthwash and toothpaste brands (Colgate, Crest and Close up) that had inhibition zone values of 5-8mm.